2020
DOI: 10.3390/w12041167
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Succession of Phytoplankton Functional Groups and Driving Factors of Cyanobacterial Blooms in a Subtropical Reservoir in South China

Abstract: Freshwater phytoplankton communities can be classified into a variety of functional groups that are based on physiological, morphological, and ecological characteristics. This classification method was used to study the temporal and spatial changes in the phytoplankton communities of Gaozhou Reservoir, which is a large municipal water source in South China. Between January 2015 and December 2017, a total of 155 taxa of phytoplankton that belong to seven phyla were identified. The phytoplankton communities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…and Cyclotella spp. With the increase in aquatic plant coverage, the light intensity was further decreased, causing the functional group Y, characterized by a relatively high surface area and adaptation to low-light conditions, to emerge as the dominant group in the HCG [62,63], with Cryptomonas spp. and Gymnodinium spp.…”
Section: Discussionmentioning
confidence: 99%
“…and Cyclotella spp. With the increase in aquatic plant coverage, the light intensity was further decreased, causing the functional group Y, characterized by a relatively high surface area and adaptation to low-light conditions, to emerge as the dominant group in the HCG [62,63], with Cryptomonas spp. and Gymnodinium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of hydrogeomorphological features in shaping cyanobacterial communities as subcommunities of the phytoplankton community was showcased in two papers of the current Special Issue. Yao et al [19] investigated a 2-year succession of cyanobacteria and eukaryotic phytoplankton functional groups in a reservoir, while Katsiapi et al [14] used a system of two recently interconnected ancient lakes to show that this recent mode of water translocation between the two lakes increased the occurrence of potentially toxic and bloom-forming cyanobacteria. Another study with a dataset covering a whole decade between 2004 and 2014 reported that cyanobacteria constituted up to 60% of the primary producer biovolume, with increased dominance after 2010 [18].…”
Section: Contributionsmentioning
confidence: 99%
“…In this direction, a deeper understanding of the mechanisms that determine cyanobacterial bloom structure and toxin production become a target for managing practices [5,6]. This Special Issue, entitled "Advancing Knowledge on Cyanobacterial Blooms in Freshwaters", includes 11 research papers [9][10][11][12][13][14][15][16][17][18][19] and aims to bring together the recent research of multiand interdisciplinary approaches from the field to the laboratory and back again, driven by working hypotheses based on any aspect from ecological theory to applied research on mitigating cyanobacterial blooms.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term suppression led to the death of most 1049 (2022) 012059 IOP Publishing doi:10.1088/1755-1315/1049/1/012059 2 marine organisms [9][10][11][12]. Changes in the marine ecosystem have disturbed the sustainability of inhabitants supporting the marine environment [13][14][15]. There are numerical reductions in populations of most shelf dwellers due to a decline in the number of dominant organisms of benthic communities such as bivalve molluscs [16,17].…”
Section: Introductionmentioning
confidence: 99%